PERANCANGAN WEBSITE PADA PROGRAM STUDI TEKNIK SIPIL FAKULTAS TEKNIK DAN ILMU KOMPUTER UNIVERSITAS ISLAM INDARGIRI - Abdul Gafur (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2017)
Issues of particular campus study programs in Information Systems scheduling and ratings contained the data redundancy. Through the website is expected to solve the problem of redundancy scheduling and assessment so that students can get the desired information through access to the website of civil enggineering at Islamic University Of Indragiri (http://ts.ftik.unisi.ac.id/) did not need to come directly to the college / Academic Division in Islamic University Of Indragiri. Profile information such as information about the university, class schedules, grades and information and announcements. So that the efficiency and effectiveness in terms of time, effort, and cost can be achieved with either. The method used in this study is based on qualitative methods and action. While the system development using SDLC with Waterfall Model. The software used is: Windows XP Professional, Macromedia Dreamweaver MX 2004 and Xampp 1.7.8. Based on the above, the result of this research is an application called: Website Development of Civil Enggineering at Islamic University Indragiri. Keywords: Academic, website, civil enggineering, SDLC